The improved performance of phosphorescent p-i-n organic light emitting diodes via enhancing hole injection and reducing triplet-polaron annihilation. (29th May 2019) - Jin, Shuting; Yu, Zeqi; Shi, Zhihua; Chen, Chunxin; Zhang, Jidong; Yang, Qingqing; Qin, Dashan
Abstract: Red phosphorescent p-i-n organic light emitting diodes (OLEDs) have been fabricated incorporating bis(1-(phenyl)isoquinoline)iridium(III)acetylacetonate doped host of N, N′-bis-(1-naphthyl)-diphenyl-1, 1′-biphenyl-4, 4′-diamine [NPB:Ir(piq)2 (acac)] and cohost of NPB and 4, 4′- N, N ′-dicarbazole-biphenyl [NPB:CBP:Ir(piq)2 (acac)]. The current efficiency based on NPB:CBP:Ir(piq)2 (acac) ( x :100- x :25 by mass) is increased than that based on NPB:Ir(piq)2 (acac) (100:25), where x  = 40, 50, 60, and 70, mostly because the CBP contributes to electron transport, decreasing the number of electrons conducted by Ir(piq)2 (acac) and thereby relieving triplet-polaron annihilation. Compared to MoO3 p-doped NPB (NPB:MoO3 ), the combined MoO3 p-doped CBP (CBP:MoO3 ) and NPB:MoO3 enhances hole current into emissive layer, mainly due to the fact that the hole injection from indium tin oxide (ITO) to CBP:MoO3 is more efficient than that from ITO to NPB:MoO3 . The device applying NPB:CBP:Ir(piq)2 (acac) (60:40:25) and CBP:MoO3 /NPB:MoO3 shows comparable current density versus voltage curve while increased current efficiency than the one employing NPB:CBP:Ir(piq)2 (acac) (50:50:25) and NPB:MoO3 . The current research provides some insight to optimize the architectures of phosphorescent p-i-n OLEDs.